Seasonal Variation in Plant Polyphenols and Related Bioactivities across Three Years in Ten Tree Species as Visualized by Mass Spectrometric Fingerprint Mapping - Vanhakylä Suvi; Salminen Juha-Pekka (MDPI, 2025)
The currently changing climates and environments place plants under many types of stresses that affect both their survival and levels of chemical defenses. The gradual induction of defenses in stressed plant populations could be monitored on a yearly basis unless a seasonal and yearly variation in natural defense levels obscures such monitoring schemes. Here, we studied the stability of the species-specific polyphenol composition and content of 10 tree species over three growing seasons using five replicate trees per species. We specifically measured hydrolyzable tannins (galloyl and hexahydroxydiphenoyl derivatives), proanthocyanidins (procyanidins and prodelphinidins), flavonols (kaempferol, quercetin and kaempferol derivatives) and quinic acid derivatives with the group-specific UHPLC-DAD-MS/MS tool, together with two bioactivities, the protein precipitation capacity and oxidative activity. With the help of a fingerprint mapping tool, we found out that species differed a lot in their seasonal and between-year variation in polyphenols and that the variation was also partially specific to compound groups. Especially ellagitannins tended to have declining seasonal patterns while the opposite was true for proanthocyanidins. Some of the species showed minimal variation in all measured variables, while others showed even induced levels of certain polyphenol groups during the 3-year study. For every species, we found either species-specific baseline levels in qualitative and quantitative polyphenol chemistry or the compound groups with the most plasticity in their production. The used tools could thus form a good combination for future studies attempting to monitor the overall changes in polyphenol chemistry due to various biotic or abiotic stress factors in plant populations or in more controlled environments.